Productivity of Planting Double Cuttings - Raxmonberdiyev Vaxobdjon Karimovich; Rajabov Narzulla Orolovich; Xaydaraliyev Javohir Ravshanali o’g’li (Zien Journals, 2023)
In the article is considered the tasks of efficiency the plaring double cuttings on the territory of Uzbekistan. Author points out that for difficult rooted sorts of mulberry tree with densely wooden trees as Balhi tut, Tadjikseedless is the most productive
Keywords: cuttings; banding; callus; sorts